2017
DOI: 10.5847/wjem.j.1920-8642.2017.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metronome rates on the quality of bag-mask ventilation during metronome-guided 30:2 cardiopulmonary resuscitation: A randomized simulation study

Abstract: BACKGROUND: Metronome guidance is a feasible and effective feedback technique to improve the quality of cardiopulmonary resuscitation (CPR). The rate of the metronome should be set between 100 to 120 ticks/minute and the speed of ventilation may have crucial effect on the quality of ventilation. We compared three different metronome rates (100, 110, 120 ticks/minute) to investigate its effect on the quality of ventilation during metronome-guided 30:2 CPR.METHODS: This is a prospective, randomized, crossover ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
5
0
2
Order By: Relevance
“…Nearly half of all respondents could not guarantee a ventilation frequency of 10 breaths per minute as required, and most of them had hyperventilation, which is consistent with prior studies. [16,17] What about using a ventilator? At present, there are no recommendations for the best mechanical ventilation strategy during CPR.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly half of all respondents could not guarantee a ventilation frequency of 10 breaths per minute as required, and most of them had hyperventilation, which is consistent with prior studies. [16,17] What about using a ventilator? At present, there are no recommendations for the best mechanical ventilation strategy during CPR.…”
Section: Discussionmentioning
confidence: 99%
“…This overall survival rate was lower than the previously reported rates in countries with developed EMS systems. [9,10] In the future, we can train more people to perform bystander CPR, and introduce AEDs in ambulances and public places.…”
Section: Discussionmentioning
confidence: 99%
“…Na et al [16], adopted to the 30:2 compression to ventilation ratio, performed ventilations according to different compression rates (e.g. 100, 110, 120 compressions/min).…”
Section: Ventilation Rate and Volumementioning
confidence: 99%
“…They reported that as the speed of the metronome rhythm increased, the quality of ventilation decreased. In addition, they recommended a chest compression rate of 100/min in case of a respiratory etiology [16].…”
Section: Ventilation Rate and Volumementioning
confidence: 99%
See 1 more Smart Citation